2016
DOI: 10.1016/j.envint.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral difficulties in 7-year old children in relation to developmental exposure to perfluorinated alkyl substances

Abstract: Background Perfluorinated alkyl substances (PFAS) are suspected endocrine disruptors that are highly persistent and neurotoxic in animals. Human epidemiological studies of exposure-related deviations of children’s behaviors are sparse. We assessed the associations between prenatal, 5- and 7-year PFAS exposures and behavioral problem scores in 7-year Faroese children. Methods Concentrations of perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), and perfluorodecanoic acid (PFDA), perfluorooctane sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 59 publications
3
62
1
3
Order By: Relevance
“…No differences were reported for <13 years old children from USA, 0-18 years old "non-adults" from China, and 5 year-old children from the Faroe Islands. 24,61,62 Similarly as in the present study, higher PFOS and PFOA concentrations in boys than in girls (1-18 years) were reported in a population with high PFOA exposure from DW in the USA, 54 and similar results were observed for PFHxS and the linear isomer of PFOS in 3-11 years old children participating in NHANES 2013-14 in the USA. 63 However, in the latter case no differences were observed for PFOA (linear isomer), PFNA and PFDA.…”
Section: Resultssupporting
confidence: 88%
“…No differences were reported for <13 years old children from USA, 0-18 years old "non-adults" from China, and 5 year-old children from the Faroe Islands. 24,61,62 Similarly as in the present study, higher PFOS and PFOA concentrations in boys than in girls (1-18 years) were reported in a population with high PFOA exposure from DW in the USA, 54 and similar results were observed for PFHxS and the linear isomer of PFOS in 3-11 years old children participating in NHANES 2013-14 in the USA. 63 However, in the latter case no differences were observed for PFOA (linear isomer), PFNA and PFDA.…”
Section: Resultssupporting
confidence: 88%
“…The maternal serum concentrations of PFASs are comparable to those reported in Europe and North America though the mixture profiles vary among populations (Casas et al 2015; Shapiro et al 2016; Zhang et al 2015). PFOS and PFOA have been widely used in the past 60 years in consumer products and industrial applications due to their oil and water repellent properties (Grandjean and Clapp 2014), and while PFOS exposure has decreased in the past decade, exposure to other PFASs (e.g., PFNA and PFHxS) has emerged (Kato et al 2011; Oulhote et al 2016). In regard to mercury exposure, 30% to 65% of mothers in our study have hair concentrations above the recommended safety limits of 1.0 μg/g and 0.58 μg/g, which is a lower proportion compared to Southern European countries, but higher than in most other EU regions (Bellanger et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in ADHD prevalence in males and females (Polanczyk et al 2007), as well as the differential associations by sex of PFAS with behavioral problems and ADHD observed in previous studies (Oulhote et al 2016;Quaak et al 2016;Stein et al 2014), we additionally presented the estimates stratified by sex. By using pooled analyses of individual-level data, we added an interaction term for sex (cutoff for significance was p < 0:10) to evaluate possible effect-modification by sex.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Moreover, a total of four studies reported sex-specific associations, with girls having higher prevalence of ADHD than boys in association with PFASs (Lenters et al 2019;Oulhote et al 2016;Quaak et al 2016;Stein et al 2014).…”
Section: Introductionmentioning
confidence: 99%